Managing expectations. (how IS departments manage user expectations about data warehousing) (includes related article on managing corporate databases) - Stedman, Craig (Computerworld, 1997)
IS managers increasingly are finding that it is very difficult to create a single data warehouse to meet corporate and user requirements. Typically, IS groups are building a variety of one-subject data markets for departments, or they are creating complete data warehouses. The challenge for IS is to manage limited resources and ensure that the combination of data warehouses does not negatively impact production systems or provide users with data that is not consistent. Long development cycles for the data mart or data warehouse projects results from project complexity. In addition, IS operations often have to get help from outside to cope with increased workloads. Experienced IS personnel contend that creating data warehouses is really a management issue.